2008
DOI: 10.1021/bm700511d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies of Side Chain Effect on the β-1,3-d-Glucan Triple Helix in Aqueous Solution

Abstract: beta-1,3-D-glucans have been isolated from fungi as right-handed 6(1) triple helices. They are categorized by the side chains bound to the main triple helix through beta-(1-->6)-D-glycosyl linkage. Indeed, since a glucose-based side chain is water soluble, the presence and frequency of glucose-based side chains give rise to significant variation in the physical properties of the glucan family. Curdlan has no side chains and self-assembles to form an water-insoluble triple helical structure, while schizophyllan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…3). The stoichiometry for the interaction between GNBP3-Nter and laminarin was close to a ratio of 1-3 (n ϭ 2.51), consistent with a triple helix organization of the laminarin in solution (39). The binding affinity is K A ϭ 2.12 ϫ 10 6 Ϯ 0.4 ϫ 10…”
Section: Resultssupporting
confidence: 53%
“…3). The stoichiometry for the interaction between GNBP3-Nter and laminarin was close to a ratio of 1-3 (n ϭ 2.51), consistent with a triple helix organization of the laminarin in solution (39). The binding affinity is K A ϭ 2.12 ϫ 10 6 Ϯ 0.4 ϫ 10…”
Section: Resultssupporting
confidence: 53%
“…To investigate the ␤-1,3-glucanrecognition mechanism by ␤GRP N102, the surface plasmon resonance (SPR) data were first analyzed. In aqueous solution, ␤-1,3-glucan forms a stable triple-helical structure and is known to be converted into a random coil or a single helix by chemical or physical treatments (18)(19)(20). Previous studies have shown that NaOH treatment alters the structure of laminaran (soluble ␤-1,3-glucan) from a triple-helical structure into a partially opened triple-helical structure, and it was indicated that even after neutralization, the partially opened structure was maintained for up to 20 days (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the presence of the O-and N-linked mannosyl proteins at the Candida cell surface is required for proper priming, supposedly by aiding cell priming by an additional cell wall component. Of note, although, under aqueous conditions, long chains of purified b-glucan form a right-handed triple helical complex that is required for the proper binding to pattern recognition receptors (27)(28)(29), purified mannan might not have the required structure to be recognized by its receptor, offering an alternative explanation for the lack of priming induced by pure mannans. Different biological effects of mannans were reported, including induction of proinflammatory cytokines (19,30) and of IL-10 (31).…”
Section: Discussionmentioning
confidence: 99%